The Impact of Social Business on the Development of Communities’ Social Capital - Ramaškienė, Laura; Šumskienė, Eglė (Socialinė teorija, empirija, politika ir praktika, 2020)
There have been a lot of interest in social economics development in Europe, and social business has stood out for its social impact, having a potential approach to such societal problems as social exclusion, poverty, unemployment. The creation of social capital and social entrepreneurship are related by positive social change and economic benefits, which are achieved through personal and community bonding, innovation, and social initiatives. Social business has stood out for its social impact, having a potential approach to such societal problems as social exclusion, poverty, unemployment. The aim of the present article is to reveal social entrepreneurship impact on building social capital in Lithuanian communities. For this reason, a qualitative study was conducted based on social business activities related to community change, as well as identifying the interrelations between social business and social capital. This article introduces the theoretical approach of concepts social capital and community, followed by discussion of social business benefits and impact on the growth of community’s social capital. The results of the analysis of the research data were analytically coded based on grounded theory methodology and reveals the potential and perspective of social business in creating social change in the community following by building new relationships, trust and values, and new norms for community development. The positive changes initiated by social business are relevant to the goals of social work and reveal the need of further research in this field.
Keywords: social business; social capital; social change; community